MANAGEMEN KEUANGAN INTERNASIONAL DALAM PERUSAHAAN MULTINASIONAL - Dasopang, Nur Sania (STAI Darul Qalam Tangerang, 2023)
The purpose of this research is to know financial management International in multinational companies. This research is library research, where the theoretical sources are from books and journals as well as data and information from various other secondary data analyzed to answer the problems studied. Research result found that international financial management within the company multinational is a company's activities including analysis and activities control over financial activities related to how to obtain funds, use funds, and manage assets accordingly with company goals and objectives